The effectiveness of chemical solutions on the removal of carbaryl residues from cucumber and chili presoaked in carbaryl using the HPLC technique. (30th March 2020) - Ruengprapavut, Sutarnthip; Sophonnithiprasert, Thanet; Pongpoungphet, Napapan
Highlights: The effects of five washing solutions on cucumber and chili are compared. Washing in 0.001% KMnO4 is the most effective method of removing carbaryl residue. Washing in DI water is the least effective method of removing carbaryl residue. Carbaryl residue detected on the cucumber decreased by 64%. Carbaryl residue detected on the chili decreased by 28%. Abstract: This research aimed to compare the efficiency of five washing solutions (0.9% NaCl, 0.1% NaHCO3, DI water, 0.001% KMnO4, and 0.1% acetic acid) for removing carbaryl residues from cucumber and chili. The vegetables were soaked in 10 mg/L of carbaryl solution for 30 min and then washed for 30 min in one of the five washing solutions and the results compared. Each experiment was performed in triplicate and the amounts of carbaryl residues remaining were determined using high-performance liquid chromatography (HPLC). The results showed that 0.001% KMnO4 was the most effective at removing carbaryl from both vegetables. Washing with 0.001% KMnO4 reduced carbaryl residues to 64% and 28%, respectively, of the original concentrations. Washing with DI water was the least effective method of removing carbaryl residues. Hopefully, the results will encourage further research, into reducing carbaryl contamination by washing with chemical solutions, which will enable producers to reduce pesticide residues.